DOI: 10.31274/etd-180810-4791
|View full text |Cite
|
Sign up to set email alerts
|

Amylolysis of eight different starches with four different species of alpha-amylase

Abstract: I would like to thank Dan Falconer for always being a good sport to bounce ideas off of.Rupendrea Mukerjea was a great laboratory supervisor who was very knowledgeable. I would like to thank Dr. John Robyt for taking me on in his lab. I am grateful for Richard Honzatko for taking me under his supervision when health issues resulted in the lab disintegrating. I am indebted to the Iowa State Chemistry Department and Dr. Jesudoss Kingston for hiring me and promoting me so I would have a job, but one that did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It has been shown that environmental conditions, particularly temperature, have a significant impact on starch granules’ crystallinity, and subsequently on digestion, starch granule dimensions, and amylopectin structure, via deactivation of some enzymes [ 15 ]. Interspecies difference of starch properties are well known and often are taken into account in the nutrition industry [ 13 , 16 ]. As for intraspecies differences, they are less studied.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that environmental conditions, particularly temperature, have a significant impact on starch granules’ crystallinity, and subsequently on digestion, starch granule dimensions, and amylopectin structure, via deactivation of some enzymes [ 15 ]. Interspecies difference of starch properties are well known and often are taken into account in the nutrition industry [ 13 , 16 ]. As for intraspecies differences, they are less studied.…”
Section: Discussionmentioning
confidence: 99%